The Role of Neutrophils and Neutrophil Elastase in Pulmonary Arterial Hypertension - Taylor, Shalina; Dirir, Omar; Zamanian, Roham T.; Rabinovitch, Marlene; Thompson, A. A. Roger (Frontiers in Medicine, 2018)
Pulmonary arterial hypertension (PAH) is a severe vasculopathy characterized by the presence of fibrotic lesions in the arterial wall and the loss of small distal pulmonary arteries. The vasculopathy is accompanied by perivascular inflammation and increased protease levels, with neutrophil elastase notably implicated in aberrant vascular remodeling. However, the source of elevated elastase levels in PAH remains unclear. A major source of neutrophil elastase is the neutrophil, an understudied cell population in PAH. The principal function of neutrophils is to destroy invading pathogens by means of phagocytosis and NET formation, but proteases, chemokines and cytokines implicated in PAH can be released by and/or prime and activate neutrophils. This review focuses on the contribution of inflammation to the development and progression of the disease, highlighting studies implicating neutrophils, and neutrophil elastase and other neutrophil proteases in PAH. The roles of cytokines, chemokines and neutrophil elastase in the disease are discussed and we describe new insight into the role neutrophils potentially play in the pathogenesis of PAH.